2017
DOI: 10.1016/j.nicl.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Independent value added by diffusion MRI for prediction of cognitive function in older adults

Abstract: The purpose of this study was to determine whether white matter microstructure measured by diffusion magnetic resonance imaging (dMRI) provides independent information about baseline level or change in executive function (EF) or memory (MEM) in older adults with and without cognitive impairment. Longitudinal data was acquired from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study from phases GO and 2 (2009–2015). ADNI participants included were diagnosed as cognitively normal (n = 46), early mild co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
3
22
1
Order By: Relevance
“…Our findings suggested that by differentiating the subtypes of AD, we could achieve a finer view in interpreting the data. Our work corresponds with earlier cross-sectional studies ( Grieve et al, 2007 ; Bennett and Madden, 2014 ) and expands the longitudinal study ( Scott et al, 2017 ) by illustrating the effect of latent factors on longitudinal cognitive decline of multi-domain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings suggested that by differentiating the subtypes of AD, we could achieve a finer view in interpreting the data. Our work corresponds with earlier cross-sectional studies ( Grieve et al, 2007 ; Bennett and Madden, 2014 ) and expands the longitudinal study ( Scott et al, 2017 ) by illustrating the effect of latent factors on longitudinal cognitive decline of multi-domain.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning previous DTI studies on the same ADNI dataset, though cross-sectional studies ( Grieve et al, 2007 ; Bennett and Madden, 2014 ) showed the association between WM impairment measured by DTI metrics and executive function decline, yet longitudinal study ( Scott et al, 2017 ) suggested the insensitivity of DTI metrics to reveal the changing rate of cognitive decline. Our study, based on the same dataset, revealed that the long fibre bundle factor was more associated with EF decline rate than the other two latent WM impairment factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The interrelated white and grey matter variations were additionally linked to a decrease in executive function, as assessed by the Trail Making tests. This latter observation is however not surprising since such functional decrease has already been documented in patients with low CMRGlc within temporal and parietal areas, as well as in those with white matter lesions, and presumably linked to an impaired connectivity with the frontal grey matter areas ( Ewers et al, 2014 , Scott et al, 2017 ).…”
Section: Discussionmentioning
confidence: 56%
“…Diffusion tensor imaging (DTI) is ideally suited for the study of cortical disconnection as it provides indices of structural integrity within interconnected neural networks. It also has the potential to capture broad inter-regional white matter connectivity properties that give rise to successful cognitive function, and thus is a promising candidate predictor of future cognitive function declines (Scott et al, 2017) (Bennett & Madden, 2014a). In the cognitively normal subjects, reduced WM microstructure is linked to poorer cognitive performance, and generally find stronger relationships between white matter microstructure and cognitive function (Madden et al, 2012).…”
Section: Introductionmentioning
confidence: 99%